Pengaruh Kompetensi dan Budaya Kerja terhadap Kinerja Pengurus RW Kelurahan Cibadak - Abdul Aziz (Al-DYAS, 2026)
The performance of RW administrators as part of community organizations at the local level plays an important role in supporting the quality of public services and the effectiveness of urban village government administration. However, the performance of RW administrators in Cibadak Urban Village, Bandung City, still faces challenges, particularly in the aspects of work innovation, understanding of main duties, motivation, and independence in carrying out tasks. This study aims to analyze the effect of competence and work culture on the performance of the RW administrative unit in Cibadak Urban Village. This study used a quantitative approach with a field research design. Data were collected through the distribution of questionnaires to 85 respondents who were RW administrators in Cibadak Urban Village, then analyzed using multiple linear regression with the assistance of the Statistical Package for the Social Sciences (SPSS) for Windows Release 25. The results show that competence and work culture simultaneously have a significant effect on performance, with a coefficient of determination of 79.4%. Partially, competence has no significant effect on performance, whereas work culture has a significant effect and becomes the more dominant variable influencing performance, with a contribution comparison of 22.55% and 56.85%. These findings indicate that improving the performance of RW administrators is determined not only by individual ability but also by the strengthening of work culture, such as service orientation, discipline, responsibility, cooperation, and adaptability. The conclusion of the study affirms that work culture is the main factor in improving the performance of RW administrators in Cibadak Urban Village. The implications of this study provide practical contributions for urban village governments and community organizations in strengthening work culture, improving understanding of main duties, and encouraging independence and work innovation to improve the quality of service performance at the local level.